Listen & Communicate Book One (Part A). English as a Second Language. Supplemental Exercises. Courses 201-202. Field Test Copy - Bright, Jeffrey P.; Leibman, Suzanne; Chicago City Colleges, IL. Chicago Urban Skills Inst. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This book is designed to provide supplemental instructional materials for the "Adult Education Guide to ESL (English as a Second Language) Curriculum." Each unit covers several communications objectives outlined in the "Guide." The materials are intended for use along with both teacher-made and commercial materials. Materials are provided for two courses. The six units in Course 201 cover such topics as introducting and identifying oneself and others, greeting and saying goodbye, following classroom instruction, numbers, spelling, classroom objects, commands, money, expressing (not) understanding, family, and asking for emergency assistance. The five units in Course 202 address time expressions, describing daily routines, describing locations, identifying food, expressing likes and dislikes, asking for repetition or clarification, describing things, asking for things, identifying clothing, and describing physical/emotional state. Exercises are provided for each sub-unit within the unit. Listening, speaking, grammar, reading, and writing exercises are included. (YLB)
ERIC Note: For the teacher's guide to the ESL curriculum, see CE 044 909.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Communication Skills; English (Second Language); Grammar; Language Skills; Learning Activities; Listening Skills; Reading Skills; Second Language Instruction; Second Language Learning; Speech Skills; Writing Skills; Guides, Classroom -- Learner